2014
DOI: 10.1038/bjc.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Identifying microRNAs regulating B7-H3 in breast cancer: the clinical impact of microRNA-29c

Abstract: Background:B7-H3, an immunoregulatory protein, is overexpressed in several cancers and is often associated with metastasis and poor prognosis. Here, our aim was to identify microRNAs (miRNAs) regulating B7-H3 and assess their potential prognostic implications in breast cancer.Methods:MicroRNAs targeting B7-H3 were identified by transfecting two breast cancer cell lines with a library of 810 miRNA mimics and quantifying changes of B7-H3 protein levels using protein lysate microarrays. For validations we used we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 52 publications
7
88
1
Order By: Relevance
“…Both the studies of Pan et al (11) and Ohlsson Teague et al (12) revealed that miR-29c was differentially expressed in the eutopic and ectopic endometrium. miR-29c belongs to the miR-29 family, and it has been suggested to be downregulated in certain types of cancer (13)(14)(15)(16). In the present study, the expression levels of the miR-29 family in the endometrium samples from women without endometriosis, as well as in paired ectopic and eutopic endometrial tissue samples from patients with endometriosis were examined by RT-qPCR.…”
Section: Discussionmentioning
confidence: 92%
“…Both the studies of Pan et al (11) and Ohlsson Teague et al (12) revealed that miR-29c was differentially expressed in the eutopic and ectopic endometrium. miR-29c belongs to the miR-29 family, and it has been suggested to be downregulated in certain types of cancer (13)(14)(15)(16). In the present study, the expression levels of the miR-29 family in the endometrium samples from women without endometriosis, as well as in paired ectopic and eutopic endometrial tissue samples from patients with endometriosis were examined by RT-qPCR.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, high levels of hsa-miR-342-5p [72, 73] and -34a [74, 75] have been correlated to breast cancer decreased recurrence and increased survival; whereas low levels have been associated with cell death inhibition and therapy resistance. The hsa-miR-22 [76, 77] and members of the hsa-miR-29 family (-29a, -29b and -29c) [55, 78] – previously identified as tumour suppressors – have also been implicated in increased survival [78] and pointed out as promising prognostic biomarkers [77, 79]. …”
Section: Discussionmentioning
confidence: 99%
“…Our observations extended earlier reports on the role of these miRNAs in BC. [22][23][24][25][26] Previous reports on miRNAs in BC included studies on the plasma level of miRNAs miR-210, miR-21, miR-29a, and miR-126, 10b using real-time PCR. 22,23 They found plasma miR-210, 10b levels to be higher in patients with BC, which is in agreement with our study.…”
Section: Discussionmentioning
confidence: 99%